2015
DOI: 10.1523/jneurosci.0498-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

IL-1  Gene Deletion Protects Oligodendrocytes after Spinal Cord Injury through Upregulation of the Survival Factor Tox3

Abstract: Spinal cord injury (SCI) causes the release of danger signals by stressed and dying cells, a process that leads to neuroinflammation.Evidence suggests that inflammation plays a role in both the damage and repair of injured neural tissue. We show that microglia at sites of SCI rapidly express the alarmin interleukin (IL)-1␣, and that infiltrating neutrophils and macrophages subsequently produce IL-1␤. Infiltration of these cells is dramatically reduced in both IL-1␣Ϫ / Ϫ and IL-1␤ Ϫ / Ϫ mice, but only IL-1␣ Ϫ /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 63 publications
2
51
0
Order By: Relevance
“…Our results concur with other studies using the same setting of 50‐kdyn force impact and mouse impactor tips that indicate a moderate injury of contusion injury (Bastien et al. ). After 3 and 10 days in culture, the high numbers of live cells in the slices indicated the cells survived after the impact, although dead cells were also observed (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Our results concur with other studies using the same setting of 50‐kdyn force impact and mouse impactor tips that indicate a moderate injury of contusion injury (Bastien et al. ). After 3 and 10 days in culture, the high numbers of live cells in the slices indicated the cells survived after the impact, although dead cells were also observed (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…, ; Bastien et al . ). There is activation of microglia in the cord, even distal from the site, associated with tissue reorganization and impediment of functional recovery (Hansen et al .…”
Section: Classic Examples Of Neuroinflammation In the Context Of Centmentioning
confidence: 97%
“…Using mRNA isolated from 1d post-injection spinal cords, quantitative real-time PCR revealed that LPS with or without iron significantly increased transcription of inducible nitric oxide synthase (iNOS, ~400-fold; Fig 12A), tumor necrosis factor alpha (TNFα, ~6-fold; Fig 11B), interleukin-1 alpha (IL-1α, ~20-fold; Fig 12C) and interleukin-1β (~5-fold; not shown), all factors that contribute to neuron and/or OL toxicity (Fig. 12A–C; Li et al, 2005 & 2008; Bastien et al, 2015). Cultured microglia were similarly treated to examine direct effects of LPS and iron.…”
Section: Resultsmentioning
confidence: 99%